Do different sources of sexuality education contribute differently to sexual health and well-being outcomes? Examining sexuality education in Spain and Portugal - L. Rodrigues, David (2024)
This research was supported by grants from the International Association for Relationship Research (IARR 2022 Geographical Diversity Research Grants) and the Social Observatory of the “la Caixa” Foundation (Ref.: CF/PR/SR20/52550001) awarded to DLR, and from the Fundação para a Ciência e a Tecnologia awarded to DLR (Ref.: 2020.00523. CEECIND) and ACC (Ref.: 2023.01784.BD).